Determinación de la prevalencia de anaplasmosis, babesiosis y tripanosomiasis en el hato lechero de la hacienda Jhomar, cantón Pedro Vicente Maldonado, enero y febrero, 2015 - Oñate Bravo, Yessenia Andrea (2015)
The following study was conducted on the JHOMAR cattle farm, located in the Pedro Vicente Maldonado Canton at the northwest part of PICHINCHA Province; to determine the prevalence of hemoparasites specifically Anaplasma spp., Babesia spp. and Trypanosoma evansi; also check if there is a relationship between the presence of blood parasites with the following parameters: Hematocrit, Total Serum Protein and hematuria. 130 blood samples of 65 cows were taken, conformed by 65 samples of peripheral blood and 65 samples of capillary blood; to find if you can see hemoparasites in the different blood samples. A comparison of the results of capillary blood and peripheral blood showed that there are no significant differences, therefore the two samples show the existence of hemoparasites. The identification of the hematozoarios was carried out by fine droplet sanguine smear, exposed to Giemsa staining technique; Hematocrit was measured by venous bloodsamples with EDTA; the TSP was evaluated in venous blood without EDTA; and the hematuria was analyzed in urine samples exposed to urine test strips. According to the results obtained a prevalence of 23.1% (15/65) of hematozoa; the 93.3% corresponds to the genus Anaplasma spp.; 6.7% to the genera Anaplasma spp. and Babesia spp.; and 0% to the genus Trypanosoma evansi. According to animal distribution, 53.3% of cattle production presented Anaplasma spp.; 13.3% of calves showed that genus; the 26.7% of dry cattle is infected with Anaplasma spp.; and 6.7% of dry cattle showed the genus Babesia spp. It found no significant difference in relation to the presence of hemoparasites and other parameters studied